Cortical Gene Expression in Spinal Cord Injury and Repair: Insight into the Functional Complexity of the Neural Regeneration Program - Kruse, Fabian; Bosse, Frank; Vogelaar, Christina F.; Brazda, Nicole; Küry, Patrick; Gasis, Marcia; Müller, Hans Werner (Frontiers in Molecular Neuroscience, 2011)
Traumatic spinal cord injury (SCI) results in the formation of a fibrous scar acting as a growth barrier for regenerating axons at the lesion site. We have previously shown (Klapka et al., 2005) that transient suppression of the inhibitory lesion scar in rat spinal cord leads to long distance axon regeneration, retrograde rescue of axotomized cortical motoneurons and improvement of locomotor function. Here we applied a systemic approach to investigate for the first time specific and dynamic alterations in the cortical gene expression profile following both thoracic SCI and regeneration-promoting anti-scarring treatment (AST). In order to monitor cortical gene expression we carried out microarray analyses using total RNA isolated from layer V/VI of rat sensorimotor cortex at 1-60 days post-operation (dpo). We demonstrate that cortical neurons respond to injury by massive changes in gene expression, starting as early as 1 dpo. AST, in turn, results in profound modifications of the lesion-induced expression profile. The treatment attenuates SCI-triggered transcriptional changes of genes related to inhibition of axon growth and impairment of cell survival, while upregulating the expression of genes associated with axon outgrowth, cell protection and neural development. Thus, AST not only modifies the local environment impeding spinal cord regeneration by reduction of fibrous scarring in the injured spinal cord, but, in addition, strikingly changes the intrinsic capacity of cortical pyramidal neurons towards enhanced cell maintenance and axonal regeneration.